THE ROLE OF SPIRITUALITY ON SANTRI COMMUNICATION LEVELS IN ISLAMIC BOARDING SCHOOL OF JAGAD ‘ALIMUSSIRRY SURABAYA SURABAYA - Mutmainah, Dewi (http://jagadalimussirry.com/, 2019)
This study aims to explain the role of spirituality on the communicative level of students in the Islamic Boarding School Jagad ‘Alimussirry Surabaya. The research method used is descriptive qualitative. The study was conducted on all students of the Islamic Boarding School Jagad ‘Alimussirry Surabaya and teachers / teachers in a vulnerable period of one semester. Data obtained from questionnaires and observations that have been transcribed, then described in detail according to existing phenomena. The results showed that the role of spirituality on the communicative level of students had a significant influence. Not only for the sake of getting closer to God, but also to improve morals (both to God and His creatures), and to achieve ultimate peace of self and the environment. This is evidenced by the communicative data of students both with fellow students, teachers, and with the natural surroundings.